Historical aspects and current understanding of the connections and implications of viruses and diabetes: A narrative review - Dr Jayakrishnan B (Elsevier, 2022)
The continued increase in diabetes indicates it to be a significant global challenge to the health and wellbeing of people. Hyperglycemia is linked to chronic inflammatory processes and diabetes-related vulnerability to infection. There is historic evidence linking viruses and microbes with diabetes and in some instances considered the causative agent. The viral infection causes inflammation and autoimmune destruction of beta cells, which, in turn, give rise to hyperglycemia, finally leading to diabetes. This review considers the historic aspects of viruses and diabetes, immune dysfunction with hyperglycemia, bidirectional relations between COVID-19 virus and diabetes, and new-onset diabetes in COVID-19.